2013
DOI: 10.1371/journal.pbio.1001502
|View full text |Cite
|
Sign up to set email alerts
|

The ING1a Tumor Suppressor Regulates Endocytosis to Induce Cellular Senescence Via the Rb-E2F Pathway

Abstract: An age-associated isoform of ING1, ING1a, induces cell senescence by altering endocytosis, subsequently activating the retinoblastoma tumor suppressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 80 publications
(91 reference statements)
1
39
0
Order By: Relevance
“…Conversely, EGCG may directly inhibit DNMT activity, inducing reactivation of methylationsilenced genes as previously reported (10,(31)(32)(33)(34). Direct interaction of EGCG to the catalytic site of DNMT 1 has been reported (32), in addition to oxidation of DNMT by EGCG (20). Furthermore, inhibition of HDACs by EGCG has been reported (21).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Conversely, EGCG may directly inhibit DNMT activity, inducing reactivation of methylationsilenced genes as previously reported (10,(31)(32)(33)(34). Direct interaction of EGCG to the catalytic site of DNMT 1 has been reported (32), in addition to oxidation of DNMT by EGCG (20). Furthermore, inhibition of HDACs by EGCG has been reported (21).…”
Section: Discussionmentioning
confidence: 64%
“…Reduced p16 INK4a expression may result in sustained binding of CDK4/CDK6 to cyclin D and subsequent phosphorylation of Rb protein, resulting in uncontrolled cell proliferation (2,3). p16 INK4a expression may also mediate cell senescence (5,20); it may also inhibit cell growth by directly interacting with the eukaryotic elongation factor 1A2 (eEF1A2), reducing its expression (4). In addition, EGCG-induced apoptosis of Jurkat cells through hydrogen peroxide production has been demonstrated (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, they exert different roles since ING1a overexpression leads to a decreased histone acetylation whereas ING1b overexpression induces H3 and H4 hyperacetylation [24]. In addition, ING1a is rather involved in senescent cells pathways [25,26]. For these reasons, we will focus here on ING1b.…”
Section: Ing1 Participates In H3 and H4 Acetylationmentioning
confidence: 99%
“…They differ in their N‐termini (Fig. 1) and growth‐regulatory effects, with ING1a affecting cell senescence [64,65] and ING1b contributing to apoptosis [54,58,66–69]. Over almost two decades of study, ING1 was initially identified as a type‐II tumor suppressor, then also as an inducer of replicative senescence and more recently as a transcriptional regulator.…”
Section: Almost Two Decades Of Learning: From Candidate Tumor Suppresmentioning
confidence: 99%
“…Overexpression of human ING1 causes cell‐cycle arrest in the G 0 /G 1 ‐phase, whereas suppression leads to loss of cellular growth control and immortalisation [20]. While ING1b is mainly involved in regulating apoptosis, cellular stress, hormonal responses as well as inhibition of tumor angiogenesis [105–107], ING1a inhibits growth by inducing replicative senescence, partially through inhibiting endocytosis via the Rb‐tumor‐suppressor pathway [64,65]. ING1b can efficiently induce apoptosis through interaction with other tumor suppressors like p53 [68,108,109] and with members of the intrinsic apoptotic pathway such as BCL‐2‐associated X protein (BAX) [69].…”
Section: Almost Two Decades Of Learning: From Candidate Tumor Suppresmentioning
confidence: 99%